Design of a side-feed rectangular waveguide helical array antenna with fan-beam radiation characteristics. (September 2020) - Wu, Donghua; Liu, Xiankai; Luan, Jin; Jiang, Fujie; Tian, Yi; E, Yungang
Abstract: In the millimeter wave train-ground communication system of high-speed maglev train, train-mounted antennas are required to have the characteristics of miniaturization, wide band, circular polarization, and fan-beam radiation. A side-feed rectangular waveguide helical array antenna is designed to meet these requirements in this paper. Short axial-mode helical antenna which has compact structure and circularly polarized radiation characteristics is used as the unit antenna. To realize fan-beam radiation characteristics, this array is composed of 2×15 unit antennas. All elements are fed by a rectangular waveguide which is divided into two rectangular waveguides from the side direction of the antenna. By properly designing the length of the coupling probe in the feed system, an equal excitation amplitude distribution can be realized for all unit antennas. The radiation phase of the unit antenna can be adjusted by rotating the helix arounding its axis to realize in-phase radiation of all elements. An array antenna with a center frequency of 38.0 GHz was designed through simulation. Simulation results show that the antenna has a gain of 22.1dB, an axial ratio of 2.09dB, an elevation plane beam width of 4.4°, an azimuth plane beam width of 30.1° at 38.0GHz. In the band of 37.0-39.0GHz, the reflection coefficient of this antenna is less than -15dB, the antenna gain is greater than 21.5dB and the axial ratio is less than 2.0dB which meet the design requirements of train-mounted antenna in the millimeter wave train-ground communication system.